STUDI ANALISIS PERBANDINGAN FILLER PASIR GUNUNG DAN PASIR SUNGAI PADA CAMPURAN ASPAL AC-WC - Khoerotunnisa, Esalia; Budiman, Dedi (JITSi : Jurnal Ilmiah Teknik Sipil, 2023)
AC-WC concrete asphalt is formed from coarse aggregate, fine aggregate, asphalt as an adhesive and filler as a filler whose proportions have been determined. Filler in asphalt mixture plays an important role, especially to improve stability and reduce air voids in the mixture. The purpose of this study was able to analyze the comparison of Marshall characteristics between mountain sand filler and river sand in AC-WC asphalt mixture and was able to identify the characteristics of mountain sand and river sand. The research methods used in calculations using trial and error methods are material collection, material testing, selection of mixed aggregate gradations, asphalt content estimates, making test specimens, and Marshall tests. Marshall test results from mountain sand filler mixture at optimum asphalt content of 5.50% get density results with VIM value of 3.24%, VMA 16.81%, VFA 80.74% and for marshall parameter test results get stability values of 912 kg, flow 2.80 mm and MQ 326 kg / mm. While the river sand filler mixture with an optimum asphalt content of 6% obtained density results with VIM values of 4.50%, VMA 17.87%, VFA 74.85% and for the results of the marshall parameter test obtained stability values of 693 kg, flow 4.84 mm and MQ 143 kg / mm. KAO river filler is higher at 6% compared to mountain sand filler at 5.5%. Keywords — AC-WC, Filler, Mountain Sand, River Sand, Marshall